Increased rate of solvent diffusion in a prototypical supramolecular gel measured on the picosecond timescale. Issue 49 (4th June 2018) - Seydel, Tilo; Edkins, Robert M.; Jones, Christopher D.; Foster, Jonathan A.; Bewley, Robert; Aguilar, Juan A.; Edkins, Katharina
Abstract : Solvent diffusion in a prototypical supramolecular gel probed by quasi-elastic neutron scattering on the picosecond timescale is faster than that in the respective bulk solvent. Abstract : Solvent diffusion in a prototypical supramolecular gel probed by quasi-elastic neutron scattering on the picosecond timescale is faster than that in the respective bulk solvent. This phenomenon is hypothesized to be due to disruption of the hydrogen bonding of the solvent by the large hydrophobic surface of the gel network.